2021
DOI: 10.3390/ijerph182312302
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence and Correlates of Probable Major Depressive Disorder and Probable Generalized Anxiety Disorder during the COVID-19 Pandemic. Results of a Nationally Representative Survey in Germany

Abstract: The aim was to clarify the prevalence and correlates of probable major depressive disorder and probable generalized anxiety disorder in the general adult population during the COVID-19 pandemic. Data were derived from a nationally representative survey (August and September 2021). In total, n = 3075 individuals took part. To quantify probable generalized anxiety disorder, the established Generalized Anxiety Disorder-7 (GAD-7; cutoff of 10) was used. Moreover, the Patient Health Questionnaire-9 (PHQ-9; cutoff o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
13
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 28 publications
(27 reference statements)
2
13
1
1
Order By: Relevance
“…However, these younger individuals particularly suffer from the pandemic. This supports very recent research showing particularly high prevalence rates of both depression and anxiety among younger individuals in Germany during the course of the pandemic [ 30 , 31 ]. Due to financial hardship in young individuals, those individuals may restrict social activities and may thus feel excluded from the society [ 30 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, these younger individuals particularly suffer from the pandemic. This supports very recent research showing particularly high prevalence rates of both depression and anxiety among younger individuals in Germany during the course of the pandemic [ 30 , 31 ]. Due to financial hardship in young individuals, those individuals may restrict social activities and may thus feel excluded from the society [ 30 ].…”
Section: Discussionsupporting
confidence: 90%
“…This supports very recent research showing particularly high prevalence rates of both depression and anxiety among younger individuals in Germany during the course of the pandemic [ 30 , 31 ]. Due to financial hardship in young individuals, those individuals may restrict social activities and may thus feel excluded from the society [ 30 ]. Given the alarming prevalence rates identified in our study and the current lack of comparable studies, future in depth studies (e.g., based on qualitative data) are needed to better understand why individuals report such high loneliness and social isolation levels.…”
Section: Discussionsupporting
confidence: 90%
“…However, representative national studies show higher scores for depression and anxiety due to the pandemic in people with migration background, presumably explained by e.g. worries about relatives living abroad, stronger impairment by travelling restrictions [ 50 , 55 ]. The stronger mental impairment may predispose people with migration background to changes in eating habits.…”
Section: Discussionmentioning
confidence: 99%
“…Hyland et al [ 20 ] reported a prevalence of 20.00% for anxiety and 22.80% for depression in the general population of the Republic of Ireland in the first week of nationwide quarantine measures in 2020. A survey of the general adult population in Germany in comparable period to our study (summer 2021) presented a prevalence of anxiety in 13.40% and prevalence of depression in 20.00% of the population[ 21 ]. Some country results report higher observed rates of anxiety and depression.…”
Section: Discussionmentioning
confidence: 88%